Personality and task interdependence as moderators for task conflict and team effectiveness - D`Silva, Jeffrey Lawrence; Ortega, Adriana; Sulaiman, Abdul Hadi (A N S I Network, 2016)
Background: Although several scholars found that team effectiveness was damaged as a result of task conflict in organizational settings, the need to recognize the critical attributes to resolve task conflict and get the team back to working effectively is pertinent. In this study, it was assessed how task conflict is related to team effectiveness. Furthermore, it was conceptualized how task interdependence and personality moderates the relationship between task conflicts related to team effectiveness. Methodology: The study used stratified random sampling with a sample size of 275 Malaysian university researchers. The Structural Equation Modeling (SEM) analysis was performed. Results: The results showed that task interdependence moderated the relationship between task conflicts and team effectiveness. Regarding to the moderating effect of personality traits, the results of this study also suggest that task conflict was less negatively related to team effectiveness with higher levels of personality traits. This study remarks important information on the interactive effect of personal and task interdependence in task-conflict and team effectiveness at higher institutions levels to help to address the issue of conflict task in teams. The results in this study have practical implications for practitioners, who should pay attention to task interdependence and personality traits and well-being of staff. Conclusion: It was identified that the most effective individuals across a variety of teams may be those who can accurately assess the expectations of peers and who can adjust their initiating interdependence behavior accordingly. The article is a novel contribution in developing team effectiveness among university researchers. Based on the results managerial suggestions and future study direction were underlined.